Experimental study of optically stimulated luminescence (OSL) dosimetry to the dose perturbation of 6MV photon beam in the presence of metal objects - Zhen, Kong Wei (Universiti Sains Malaysia, 2024)
The prevalence of metallic implants have brought significant challenges during radiation therapy due to the photon interaction with metal. Metallic implants can alter the desired dose distribution within patient bodies, resulting in dose perturbation and consequently ineffective treatment delivery. Commercial nanodot dosimeters based on Optically Stimulated Luminescence (OSL) techniques has emerged as an alternative dosimetry method in radiotherapy due to their high sensitivity, reproducibility and small sizes. This study aims to investigate the dose perturbation of high photon beam in the presence of metal objects using nanodot OSL-based dosimeters. Method: An experimental study was conducted to compare the doses and Percentage Depth Dose (PDD) measured by Markus ionization chamber and nanodot dosimeters in a 20 cm thickness solid water phantom with and without the presence of 1.0 cm lead plate, 0.5 cm and 1.0 cm aluminium plates from which the dose perturbation due to metal plates was investigated as well. Results: The p-values from the Mann-Whitney test for comparisons of measured doses and PDD between OSL and IC measurements are all greater than 0.05. However, statistical uncertainties of nanodot dosimetry system are up to 13.75%, which is greater than the desired 3% published from IAEA TRS report no 398. When measuring dose with a 0.5 cm aluminium plate, BSDF values exceed 1.0 at a depth of 4 cm (BSDF = 1.01), using 1 cm aluminium plate increase the BSDF to 1.03 at 4 cm depth. Switching to a 1 cm lead plate results in BSDF exceeding 1.0 at a depth of 2.5 cm (BSDF = 1.02). The ranges of FDPF for dose measurements with 0.5 cm and 1 cm aluminium plate are 0.96 – 0.98 and 0.93 – 0.96 respectively. The FDPF range behind the lead plate is 0.57-0.67. Conclusion: There is no a significant difference between OSL and IC dosimetry in measurements with and without metal plate. The higher uncertainties of nanodot dosimetry is due to the unsatisfied precision of the nanodot dosimetry system This research demonstrated that OSL dosimetry is effective in measuring dose perturbations, with BSDF and FDPF becoming more significant as the atomic number of the metal increases.